Pemberdayaan Perempuan melalui Pelatihan Pembuatan Mie Kering Ebi pada Masyarakat di Kabupaten Takalar - Reski Febyanti Rauf; Andi Sukainah; Muh. Rais (DEDIKASI, 2018)
One of local resources developed in the Sanrobone Village of Sanrobone Subdistrict of Takalar District isdried shrimp. The untilization and processing of dried shrimp is limited to the shrimp paste production in a smallscale. This has an impact on the low of dried shrimp management in the community as the main raw material notonly for shrimp paste, but for other food products. The program aimed to empowering community especially womento process the dried shrimp into the nutritious and value added crispy noodles of dried shrimp.The problem approachwas carried out by the partner group participation method. This method involved partners in the training process, inorder partners know, understand, implement, and evaluate. The stages of training activities include the preparationstage (observation, consolidation, socialization, and module preparation and training presentation material) andimplementation (filling out the questionnaire at the beginning and end of the training, giving material anddiscussion, demonstrations/practices, and mentoring). Evaluation of partner participation was carried out by usinginterview methods, questionnaires, discussions, observation and documentation. Data analysis was performed usingdescriptive analysis method.The result of this activity has an impact on increasing the knowledge, independence,confidence and creativity of partners in managing local resources creatively and innovatively, applying themanufacture of crispy noodles of dried shrimp as a nutritious food product and able to provide added value inimproving the economy and prosperity community in that area.